What Is Resilience and How Can It Be Nurtured? A Systematic Review of Empirical Literature on Organizational Resilience - Edwine Barasa; Rahab Mbau; Lucy Gilson (International Journal of Health Policy and Management, 2018)
Background Recent health system shocks such as the Ebola outbreak of 2014–2016 and the global financial crisis of 2008 have generated global health interest in the concept of resilience. The concept is however not new, and has been applied to other sectors for a longer period of time. We conducted a review of empirical literature from both the health and other sectors to synthesize evidence on organizational resilience.